Compulsivity in anorexia nervosa - Godier, L (2015)
Anorexia Nervosa (AN) is a psychiatric disorder characterised by persistent self-starvation, which has high mortality rates, and low rates of recovery. In conjunction with a lack of effective treatments, the serious nature of the disorder emphasises the need for research investigating the underlying processes contributing the persistence of the disorder, and the identification of novel avenues for treatment development. In individuals with AN, dietary restriction often takes on a driven and compulsive quality, with increasing suggestion of parallels with other disorders featuring compulsive behaviour, such as Obsessive-Compulsive Disorder (OCD) and substance dependence. The commonalities and comorbidities in compulsive behaviours across a range of disorders have been highlighted by Robbins et al (2012), who propose a transdiagnostic approach to compulsivity, arguing that this behavioural construct has cross-diagnostic significance. Conceptualising compulsivity in this way may aid in the development of novel research avenues investigating the learning processes and neurobiological mechanisms underpinning this behaviour. In light of this, the aim of this thesis was to investigate the compulsive nature of behaviour in AN, and the behavioural and neural underpinnings of this behaviour guided by research carried out in other compulsive disorders. Chapter 1 reviews models of the neural and behavioural underpinnings of compulsive behaviour, and discusses these in relation to compulsive behaviour in AN. Chapter 2 presents qualitative data supporting parallels between the subjective experience of compulsive behaviour in AN and substance use disorders (SUDs). These parallels are further examined in Chapter 3, in which two novel measures of compulsive weight-loss behaviour were developed and validated by adapting a questionnaire assessing addictive behaviour. Chapter 4 presents data suggesting that these parallels in behaviour do not reflect a common tendency to develop habits in learning, as found in substance dependence and OCD. The electrophysiological data presented in Chapter 5 was unable to provide evidence that AN may be underpinned by dysfunction of the neurocircuitry seen in other compulsive disorders. Whilst these studies support suggestion of parallels with substance dependence, at least at the level of self-report, the hypothesised parallels in the underlying behavioural and neural mechanisms were not found.